The removal of phosphorus from reject water of municipal wastewater treatment plant using iron ore - Guo, Cheng Hong; Stabnikov, Victor; Kuang, Shengli; Ivanov, Volodymyr M. (My University, 2009)
BACKGROUND: Reject water (return liquor) from dewatering of anaerobically digested activated sludge in municipal wastewater treatment plants contains from 10 to50%of the phosphorus load when being recycled to the aeration tank. Phosphorus removal from reject water could be an effective way to decrease phosphorus loads entering the aeration tank. An innovative approach involves the replacement of iron salts, which are commonly used for phosphorus removal, with ferrous ions produced by iron-reducing bacteria from iron ore. The aim of the research was to examine the feasibility of phosphorus removal from return liquor using bioreduction of iron ore.RESULTS: Ferrous production, phosphate and organic carbon removal rates were determined as a function of different iron ore particle sizes in batch experiments. Iron-reducing bacteria ensured the production of ferrous ions from iron ore up to concentrations of 550 mg L−1. The ferrous production rate was linearly dependent on the calculated specific surface area of the iron ore particles. The phosphorus concentration in the reject water was reduced by 90% during bioreduction of iron ore. The phosphorus removal rate did not depend on specific surface area of iron ore particles when the particle size of iron ore was smaller than 7 mm. The organic carbon removal rate did not seem to be dependent on iron ore particle size. CONCLUSION: Removal of phosphate using iron ore can be more economical than conventional chemical precipitation of phosphate using iron salts because of the lower cost of iron ore.
Keywords: iron-reducing bacteria; phosphor; залізна руда; залізо-відновлювальні бактерії; фосфор; activated sludge; активний мул; кафедра біотехнології і мікробіології